Von Recklinghausen disease/type I neurofibromatosis and its association with orofacial changes: Literature review and case report - Santos, Monah Sampaio; de-Campos, Wladimir Gushiken; Esteves, Camilla Vieira; Zambon, Camila Eduarda; Rocha, André Caroli; Machado, Gustavo Grothe; Lemos, Celso Augusto (Journal of Oral Diagnosis, 2019)
Neurofibromatosis is an autosomal dominant genetic disorder and an inherited condition. This pathology represents 90% of the cases found in the general population. Oral manifestations of neurofibromatosis type I can occur in 70 to 92% of cases, especially when a detailed clinical examination is performed associated with complementary imaging tests. Because of this, it is not uncommon for the dental surgeon to be the first health professional to perform the diagnosis of the disease. The importance of having an early diagnosis correlates with the possible complications of the disease. The carrier may have offspring that manifest the disease in its severe form because of the large capacity for variation, which can be avoided with prior genetic counseling. In this study we report a case of a woman diagnosed and treated for central giant cell lesion 44 years ago, with dental, spine and mandible alterations, also with a family history of neurofibromatosis.